EFFECTS OF THE “LONG Time DO” PROGRAM TO ENHANCE SELF-EFFICACY WITH SOCIAL SUPPORT FOR HEALTH BEHAVIORS MODIFICATION IN ABDOMINAL OBESITY AMONG HEALTH PERSONNEL - แสนเสนยา พิชญสินี; หีบแก้ว ปัดชาสุวรรณ์ นาฏนภา; บัญชรหัตถกิจ พรรณี (Primary Health Care Journal (Northeastern Edition), 2025)
Central obesity among healthcare personnel is a significant issue that impacts not only their personal health but also their credibility as role models for the public. This quasi-experimental research aimed to evaluate the effectiveness of the “LONG Time DO” program, designed to enhance self-efficacy and social support for health behavior modification among healthcare personnel with central obesity. The sample consisted of 64 healthcare personnel diagnosed with central obesity, divided into an experimental group (n=32), which participated in the 12-week program, and a comparison group (n=32), which received standard care. Data were collected at baseline and post-intervention using health behavior questionnaires and physical assessments. Statistical analyses employed descriptive statistics, Chi-square test, Independent t-test, Paired t-test, and ANCOVA. The results revealed that, post-intervention, the experimental group had significantly higher mean scores than the comparison group in outcome expectation (X̅diff = 3.04, 95% CI: 0.84 to 5.25), self-efficacy (X̅diff = 12.52, 95% CI: 9.90 to 15.13), eating behavior (X̅diff = 11.81, 95% CI: 7.53 to 16.09), and exercise behavior (X̅diff = 12.19, 95% CI: 8.99 to 15.39). Furthermore, the experimental group demonstrated a significant reduction in waist circumference (X̅diff = 5.74, 95% CI: 4.14 to 7.34) and Body Mass Index (X̅diff = 1.02, 95% CI: 0.39 to 1.65). Within-group comparisons indicated significant improvements in all variables for the experimental group, whereas the comparison group showed no significant changes. These findings suggest that the “LONG Time DO” program is effective and can be applied to develop health interventions aimed at reducing central obesity among healthcare personnel on a wider scale.